Fathers at work: Work-family conflict, work-family enrichment and parenting in an Australian cohort - Cooklin, A R; Martin, A; Strazdins, L; Nicholson, J; Westrupp, E; Giallo, R (My University, 2014)
Contemporary fathering is characterised by the combined responsibilities of earning an income and being an involved, nurturing parent. The ensuing work-family interface is likely to affect fathering behaviours. However, the relationship between work-family conflict, work-family enrichment and specific fathering behaviours known to determine children's development has not been widely investigated. Secondary data from fathers of 4-5 year old children (K-cohort, Wave 1) participating in the Longitudinal Study of Australian Children (LSAC) were analysed (N=2679). Results revealed that higher work-family conflict was associated with more irritable (β = 0.06, p<0.001), less warm (β = -0.04, p<0.01), and less consistent parenting (β = -0.07, p<0.001), when socio-demographic and child characteristics were controlled for. Protective associations were found between work-family enrichment and optimal parenting behaviours. Fathers' employed for long hours, and those who were the sole-earner in the household were most at risk of reporting high work-family conflict. Findings provide impetus for workplace and public policy to extend optimal, family-friendly employment conditions to all parents, including fathers, of young children.
Journal of Family Issues
Keywords: Employment -- Work/life Balance; Employment -- Labour force participation; Families -- Fathers; Families -- Parents and Parenting; Families and relationships; Labour market; Employment; Families; Fathers; Parents and Parenting; Labour force participation; Work/life Balance; Families and relationships; Employment and unemployment